Compondo Quadrinhos: atividades de leitura e escrita na escola - Silva Júnior, Edito Romão da (2020)
With the advancement of technology, society has been through significant transformations and along with them an infinity of new textual / discursive genres has emerged as a way of materializing language. In order to be updated with different ways of communicating, it is necessary to be inserted in the world. Therefore, it is of the upmost importance that school must work effectively with language, seeking to divide the activities of grammatical metalanguage with those aimed at reading and producing the most varied textual / discursive genres. Thus, taking into consideration language under the socio-interactional paradigm, the main goal of our research was to arouse a greater interest in students about reading and writing. In order to achieve this central objective, these following specific objectives were outlined in this research: to present a suggestion for reading and writing comic books; to make a cutout on the theme of black conscience to work on elements related to the constitution of citizen participation and racial equity; to comprehend the discourse of the students, materialized in the answers given through surveys, as well as in the final work, suggested in the intervention proposal; and finally, to instrumentalize the subjects for the production of a comic book, which emphasizes situations of overcoming racism on the part of the victims. Our choice of this genre was due to its simple and direct language; as it is structured in short narratives, which permits reading of an entire story in a short period of time, allowing greater dynamism to activities in classroom; providing thematic diversity, in addition to presenting a strong visual composition, which facilitates the encouragement of reading. These elements were rather relevant, since adolescents demonstrated difficulty with concentrating; for having, exclusively, classroom time to carry out all the suggested activities; the textual / discursive genre presents the possibility of thematic diversity, in addition to the acceptance of comic books among the subjects involved in the intervention proposal. As a theoretical contribution, according to Koch and Elias (2007), language concepts were discussed. From the perspective of Solé (1998), the ways of apprehending meanings for texts within the scope of textual / discursive genres were highlighted. Based on Marcuschi (2005), the differences between type and textual genre were presented, as well as inter-gender intertextuality. Furthermore, teaching of textual production was exposed, according to what Marcuschi (2018) affirms. Regarding methodological aspects, the didactic sequences, proposed by Dolz and Schneuwly (2011), were used to systematize the application steps. Based on Mendonça (2005), charge, cartoon, comic strips and comics were conceptualized, genres present in the hyper-genre comics. From the perspective of Ramos (2014), elements related to the aspects which build up the textual / discursive comic book genre are listed, such as the shape of balloons, onomatopoeias, movement of characters, time, space, colors, language and ways of presentation of the comics, factors that were important in this current research for the construction and analysis of the final production. Finally, for the analysis of the students' production, Bakhtin's theoretical propositions (2004) were used, concerning the compositional form, content and style that integrate the textual/discursive genre. It can be said that the didactic sequence presented significant results, since students aroused the interest in reading comic books (comics), in addition to producing them satisfactorily, with regards to aspects of compositional form, content and style.